Computational intelligence techniques for new product design - Chan, Kit Yan; Dillon, Tharam S. , 1943-; Kwong, C. K. (Studies in computational intelligence, 2012)
Using computational intelligence in product design is a fast-growing and promising research area in computer sciences and industrial engineering. These assembled papers from the CIMA 2010 workshop cover the full spectrum of topics in this exciting field